Haemodynamic evaluation of coronary artery plaques : prediction of coronary atherosclerosis and disease progression - Chaichana, Thanapong (Curtin University, 2012)
Coronary artery disease is the leading cause of death in advanced countries. Coronary artery disease tends to develop at locations where disturbed flow patterns occur, such as the left coronary artery. Haemodynamic change is believed to play an important role in the pathogenesis of coronary artery disease. This study was conducted to analyse the haemodynamic variations in the left coronary artery, with normal and diseased conditions, based on idealised human left coronary artery models and realistic reconstructed left coronary geometries. Computational fluid dynamics analysis was performed, to replicate the actual physiological conditions that reflect the in vivo cardiac haemodynamics with high resolution CT images. The wall shear stress, wall shear stress gradient, velocity flow patterns, pressure gradient, wall pressure, wall pressure gradient, wall pressure stress gradient, were calculated though in idealised but near realistic left coronary geometries during the cardiac pulsatile cycles. This novel research was performed in four stages, with Stage 1 studying the correlation between bifurcation angle and subsequent haemodynamic effects; Stage 2 focused on the position of plaques in the left coronary artery and corresponding haemodynamic variations based on realistic models; Stage 3 investigated the impact of plaques on coronary side branches based on realistic models. Stage 4 analysed individual patients with the bifurcation stenosis based on CT images.Normal coronary artery geometries were generated to investigate the haemodynamic variations of various angulations of the left coronary artery, based on idealised and actual coronary artery models. Eight idealised left coronary artery models were generated, with inclusion of different coronary angulations, namely, 120°, 105°, 90°, 75°, 60°, 45°, 30° and 15°. Four realistic left coronary artery geometries were reconstructed, based on selected patient's data, with angulations ranging from wide angulations of 110° and 120° to narrow angulations of 73° and 58°. There were twelve left coronary artery models in total which consisted of left main stem, left anterior descending and left circumflex branches. Haemodynamic analysis showed that disturbed flow patterns were observed in both idealised and realistic left coronary geometries with wider angles. Wall pressure was found to reduce when the flow changed from the left main stem to the bifurcated locations. A low wall shear stress gradient was revealed at left main bifurcations in models with wide angulations. There is a direct correlation between coronary angulations and subsequent haemodynamic changes, based on realistic and idealised geometries.Diseased coronary geometry was used to study the haemodynamic changes surrounding the bifurcation plaques based on patient’s data. High resolution CT images of the coronary plaques were used to locate and generate the position of actual plaques, which was combined with the reconstructed left coronary disease geometry. Coronary plaques were replicated and located at the left main stem and the left anterior descending to produce at least 60% coronary stenosis. Computational fluid dynamic analysis was used to investigate the haemodynamic effects with and without the presence of coronary plaques. Our results revealed that the highest pressure gradients were observed in stenotic locations caused by the coronary plaques. Low flow velocity regions were found at post-stenotic locations in the left bifurcation, left anterior descending, and left circumflex. Wall shear stress at the plaque locations was similar between the non-Newtonian and Newtonian models, although more details were observed with non-Newtonian model. There is a direct correlation between coronary plaques and subsequent haemodynamic changes, based on the simulation of plaques in the realistic left coronary geometries.Coronary artery disease with their side branches was used to analyse the change of haemodynamic factors surrounding bifurcation plaques to characterise the effect of disturbed flow to their side branches. Coronary plaques were located at the left main bifurcation, which is composed of the left main stem and the left anterior descending to generate >50% narrowing of the coronary lumen. Haemodynamic parameters were compared in the left coronary artery models, with and without the presence of plaques. The analysis demonstrated that wall shear stress decreased while wall pressure stress gradient was increased in coronary side branches due to the presence of plaques. There is a direct relationship between coronary plaques and subsequent haemodynamic changes based on the bifurcation plaques located in the realistic coronary geometries.Patient-specific models with coronary disease were used to analyse the haemodynamic variations surrounding the stenotic locations. Three sample patients with left coronary artery disease were chosen based on CT data. Coronary plaques were shown at the left anterior descending and left circumflex branches with more than 50% lumen narrowing. Wall shear stress and blood flow changes in the left coronary artery disease were calculated during cardiac pulsatile cycles. Our results showed that wall shear stress was found to increase at the stenotic regions and decrease at pre- and post-plaque regions, while the disturbed flow regions was found at post-plaque location. There is a direct effect bifurcation plaque on the changes of blood flow and wall shear stress, based on the realistic coronary disease geometries.In summary, the results of this project show that coronary angulation is directly related to haemodynamic changes, resulting in the formation of atherosclerosis, leading to coronary artery disease. Presence of coronary plaques impacts the haemodynamic changes to both the left main coronary artery, and side branches. Computational fluid dynamic analysis of realistic normal and diseased coronary models improves our understanding of the pathogenesis of coronary artery disease. Further studies are needed to correlate the haemodynamic changes in the presence of plaques with clinical outcomes in patients with suspected coronary artery disease.